2021
DOI: 10.1111/apa.16121
|View full text |Cite
|
Sign up to set email alerts
|

Endurance training may improve exercise capacity, lung function and quality of life in Fontan patients

Abstract: Univentricular heart is a complex and rare heart malformation. The incidence has been reported to be 0.39 per 1000 births. 1 The survival of children born with complex heart malformations has improved and, today, most will survive to adult age. 2,3 Children with univentricular hearts go through repeated surgical interventions, resulting in a Fontan circulation. [4][5][6][7] There is growing concern about these patients' physical performance but also about their quality of life. Deterioration of heart function,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
3
1
Order By: Relevance
“…Few other authors also reported a positive correlation between PA levels and the self-reported psychosocial functioning and general health ( 4 , 5 ). In contrast other studies did not observe any association between PA levels and parent-reported HRQoL ( 32 , 33 ). Even though data are not completely consistent, our results suggests that specific interventions targeted to increase PA levels may have some beneficial effects not only on physical aspects but also on peer and family socialization and patients cognitive development ( 8 , 9 ).…”
Section: Discussioncontrasting
confidence: 79%
“…Few other authors also reported a positive correlation between PA levels and the self-reported psychosocial functioning and general health ( 4 , 5 ). In contrast other studies did not observe any association between PA levels and parent-reported HRQoL ( 32 , 33 ). Even though data are not completely consistent, our results suggests that specific interventions targeted to increase PA levels may have some beneficial effects not only on physical aspects but also on peer and family socialization and patients cognitive development ( 8 , 9 ).…”
Section: Discussioncontrasting
confidence: 79%
“…It has been suggested that exercise training may enhance submaximal, rather than maximal, exercise capacity. 65 In our review, 3 training programs reported improved submaximal exercise parameters without significant increases in peak or maximal VO 2 consumption (Table 3 and Supplemental Figure S1). However, one of these studies focused exclusively on inspiratory muscle training without aerobic training, 46 and it is possible that isolated respiratory muscle training may not improve VO 2peak as substantially as aerobic training.…”
Section: Discussionmentioning
confidence: 82%
“…This lowers blood pressure. 12 The athlete's heart rate increases by 150 beats after doing aerobics, in which case the strength of the respiratory muscles can be increased, and the maximum oxygen intake can be increased. Increasing the hemoglobin level in the process also increases the speed of aerobic exercise.…”
Section: Discussionmentioning
confidence: 99%